How Knowledge of Ancient Egyptian Women Can Influence Today’s Gender Role: Does History Matter in Gender Psychology? - Khalil, Radwa; Moustafa, Ahmed A.; Moftah, Marie Z.; Karim, Ahmed A. (Frontiers in Psychology, 2017)
A gender role is “a set of societal norms dictating what types of behaviors are generally considered to be acceptable, appropriate, or desirable for a person based on their sex”. However, socially constructed gender roles can lead to equal rights between genders but also to severe disadvantages and discrimination with a remarkable variety between different countries. Based on social indicators and gender statistics, “women in the Arab region are on average more disadvantaged economically, politically, and socially than women in other regions”. According to Banduras’ social learning theory, we argue that profound knowledge of the historical contributions of Ancient Egyptian female pioneers in science, arts and even in ruling Egypt as Pharaohs can improve today’s gender role in Egypt and Middle Eastern countries. Therefore, this article provides an elaborate review of the gender role of women in Ancient Egypt, outlining their prominence, influence, and admiration in ancient societies, and discusses the possible psychological impact of this knowledge on today’s gender role. We suggest that future empirical research should investigate how enhancing the knowledge of women from Ancient Egypt can improve today’s gender role in Egypt and the Middle East. Bandura’s social learning theory is outlined as a possible framework for future research.